The Kappa Free Light Chains Index and Central Vein Sign: Two New Biomarkers for Multiple Sclerosis Diagnosis - Michael Levraut; Cassandre Landes-Chateau; Lydiane Mondot; Mikael Cohen; Christine Lebrun-Frenay (Neurology and Therapy)
Abstract At the last European Committee for Treatment and Research in Multiple Sclerosis (ECTRIMS) meeting, Montalban and the experts’ panel announced the 2024 revision of the McDonald criteria. The optic nerve has been added as a fifth dissemination in space (DIS) criteria topography among the main changes. Multiple sclerosis (MS) can be diagnosed in patients with radiologically isolated syndrome (RIS) if specific biomarkers are added to at least two of the five DIS criteria. Among the particular MS biomarkers, the kappa free light chain index (kFLC index) positivity will be added to oligoclonal band (OCB) detection to fulfill intrathecal immunoglobulin synthesis, and the central vein sign (CVS) will be able to ensure the specificity of the lesions detected on MRI scans. This review summarises the knowledge on the kFLC index and the CVS in people with MS and RIS, allowing them to be incorporated into the proposed revision of the McDonald criteria.